Experience of International Education of East Asian Students in English-speaking Countries: A Four-Dimensional Approach (Journal of Student Affairs in Africa, 2021)
Global participation in international education in the last two decades has increased exponentially.International students face difficulties in adjusting to the culture of their host country due to their unique needs (Bertram, Poulakis, Elsasser & Kumar, 2014). This article presents themes comprising the international education phenomenon involving the experiences of East Asian international students in English-speaking countries. The literature reviewed for this article pertains to many aspects of international education, covering the factors that influence the decision to embark on the international education journey to the adjustment experienced by students to the host culture. The authors suggest that the international education experience is comprised of four dimensions: structural, linguistic, internal, and external. We also posit that Confucianism, which many East Asian students follow, influences not only the psycho-social dimension of the international education experience but also their instructional preferences within the structural dimension. We further contend that students’ actual and perceived proficiency (or the lack thereof) in the host country’s language greatly shapes all aspects of thestudent’s international education experience, which then determines the degree of acculturative stress involved and plays a key role in each of the three dimensions. Because of the anticipated continued growth in the number of international students from EastAsia attending higher education institutions in English-speaking countries such as the United States, Australia, Canada, and parts of Africa, it is important to examine how each of the dimensions proposed impact each other. Approaching the study of the international education experience one dimension at a time, as many scholars have done, does not completely address all of the unique needs of international students. We suggest that research in this area be conducted holistically by exploring the ecology surrounding the international student. Taking this ecological approach will help clearly definethe role that home and host countries and host higher education institutions must take in serving theinternational students well.
Keywords: acculturation; campus climate; Confucianism; engagement; international education; language; psychosocial; student development